Korelasi Nilai PTS dengan Nilai PAS Pelajaran Matematika Kelas VIII SMP - Achmad Tri Sudaryadi; Ageng Triyono (Jurnal Inovasi Pendidikan Matematika (JIPM), 2022)
This study aims to determine whether or not there is a correlation between the results of the Mid-Semester Assessment and the results of the Final Semester Assessment in the mathematics subjects of class VIII students of State Junior High School 15 Purworejo in the 2021/2022 academic year. The research method used is a non-experimental quantitative research method. The research population was 160 students, with a research sample of 110 students. The normality test results showed that the data came from a normally distributed population. The homogeneity test results showed that the research sample had a homogeneous variance. The calculation of the product-moment correlation of 0.73 indicates a strong correlation between research variables. The results of hypothesis testing using t-test obtained tcount=11.03 and ttable=1.98 indicate that the correlation found is valid for the entire population. So the conclusion of this study shows a positive and significant correlation between the results of the Mid-Semester Assessment and the results of the Final Semester Assessment in mathematics subjects for students of VIII State Junior High School 15 Purworejo in the 2021/2022 academic year.